2007
DOI: 10.1016/j.euromechflu.2006.08.002
|View full text |Cite
|
Sign up to set email alerts
|

The absolute instability of the boundary layer on a rotating cone

Abstract: This paper is concerned with the existence of local absolute instability in the boundary-layer flow over the outer surface of a rotating cone, thereby extending earlier work by Lingwood who considered the rotating disk. Both still outer fluids and non-zero axial flow are considered, viscous and streamline-curvature effects are included, and the analysis is conducted for a wide range of cone half-angles, ψ. In still outer fluid our predicted local Reynolds numbers at the onset of absolute instability is relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
81
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(88 citation statements)
references
References 18 publications
(40 reference statements)
7
81
0
Order By: Relevance
“…Although numerous flow-visualization studies due to Kobayashi et al [7][8][9][10][11][12][13][14][15][16][17] and recent theoretical studies due to Garrett & Peake [18][19][20][21][22] have been published on the boundary-layer flows over rotating spheres and cones, a complete understanding of the stability characteristics of such boundary layers with regards to these applications is still a long way off. This current paper is part of a series by the present authors 23,24 which considers the convective instability of the boundary-layer flow over a family of rotating cones (including the disk as the limiting half angle), both in and out of an imposed axial flow.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although numerous flow-visualization studies due to Kobayashi et al [7][8][9][10][11][12][13][14][15][16][17] and recent theoretical studies due to Garrett & Peake [18][19][20][21][22] have been published on the boundary-layer flows over rotating spheres and cones, a complete understanding of the stability characteristics of such boundary layers with regards to these applications is still a long way off. This current paper is part of a series by the present authors 23,24 which considers the convective instability of the boundary-layer flow over a family of rotating cones (including the disk as the limiting half angle), both in and out of an imposed axial flow.…”
Section: Introductionmentioning
confidence: 99%
“…This current paper is part of a series by the present authors 23,24 which considers the convective instability of the boundary-layer flow over a family of rotating cones (including the disk as the limiting half angle), both in and out of an imposed axial flow. Particular emphasis is placed on the above applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hall [8] demonstrated that in the limit of large Reynolds number the upper and lower branches of the neutral curve can be described (with excellent agreement) using asymptotic theory. More recently, the aforementioned pioneering studies have been extended to include rotating spheres, see Garrett & Peake [9] and rotating cones, see Garrett et al [10] and Hussain et al [11]. In all cases the flow can be stabilised (or destabilised) with control of the governing parameter, that being the spin rate, in the case of the sphere, and the half-angle, in the case of the cone.…”
Section: Introductionmentioning
confidence: 99%
“…Such flows are often due to rotating bodies as, for example, disks [3,4], cones [5,6], or spheres [7]. Here, we consider a semi-infinite cylinder, rotating about its axis and placed in a high-Reynolds-number axial stream, thus inducing a steady, axisymmetric, three-velocity-component boundary layer whose flow field depends on rotation and curvature of the cylinder, as we have already described in an earlier paper [8], henceforth referred to as I.…”
Section: Introductionmentioning
confidence: 99%